SISTEM INFORMASI SELEKSI PENERIMAAN PEGAWAI DENGAN METODE WATERFALL: Employee Recruitment Selection, Information System, Waterfall - Nuris, Nuzuliarini; Ariani, Fattya (LP2M Universitas Nurdin Hamzah, 2019)
Human resources are one of the important factors in an effort to support the development of the business world. Selection of employees who still do the process manually, such as recording, still uses Microsoft Word and Microsoft Excel programs. Processing data that is quite difficult results in a delays in the process of selecting new employees, searching for data and influencing the performance of the company's internal employees. To overcome this, a better employee selection system model is needed, namely a computerized system with the waterfall method. With an employee recruitment system, selecting applications is faster and more accurate because applicants' data can be stored directly at that time can also find out whether the applicant meets the criteria or not, applicant data storage can also be minimized with a computer so that the search for the required data can be found immediately.